Immunology - Luttmann, Werner (Elsevier Academic Press, 2006)
Providing the reader with tips and tricks for lab experiments, this work explores the methodological variety of immunology, and addresses the assets and drawbacks as well as critical points. It also contains summaries of routine procedures such as column chromatography as well as listings of the advantages and disadvantages of alternative methods.